2014
DOI: 10.1111/1475-6765.12055
|View full text |Cite
|
Sign up to set email alerts
|

The electoral consequences of two great crises

Abstract: Who benefits from deep economic crises: the left, the right or neither? On the basis of evidence from elections in 1929–1933 and 2008–2013 in all states that were democracies in both periods, it is argued in this article that the electoral consequences of the Great Depression and the Great Recession were surprisingly similar: in both periods, right‐wing parties were at first more successful than left‐wing parties, although this effect only lasted for a few years. The manner in which a crisis develops over time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 33 publications
4
43
1
1
Order By: Relevance
“…In other words, they may turn to the centre‐left, if the government was on the centre‐right, or vice versa. Contrary to the analysis reported by Lindvall (), I could not find a systematic pattern of swings to the left or to the right. Whoever governed was punished – whether the government was on the centre‐left or on the centre‐right.…”
Section: Economic Votingcontrasting
confidence: 99%
“…In other words, they may turn to the centre‐left, if the government was on the centre‐right, or vice versa. Contrary to the analysis reported by Lindvall (), I could not find a systematic pattern of swings to the left or to the right. Whoever governed was punished – whether the government was on the centre‐left or on the centre‐right.…”
Section: Economic Votingcontrasting
confidence: 99%
“…Despite the election of Obama, for example, an enduring new Democratic coalition did not materialize. Conversely, despite the conservative victories in 2010, neither British nor American voters were ready to roll back the welfare state altogether (Bartels 2011, Gamble 2009, Lindvall 2011. There was anger but little real revolutionary fervor.…”
Section: The Politics Of Neoliberalismmentioning
confidence: 99%
“…Indeed, it is interesting to see whether the crisis results in issue-specific moves to the right or the left. Some observers suggested that, in the short run, parties from the right will gain votes and attract more voters, but that, in the longer run, we may expect to find a stronger move towards the left (Lindvall 2014). As indicated in the methods' section, the average position on a given issue may take values between −1 to +1.…”
Section: Positions Adopted On These Issuesmentioning
confidence: 97%